NOx Emissions Cost Assessment Due to Rapid Mass Transport Development Plan (Tram) in Surabaya - Mochammad Choirul Rizal; Hera Widyastuti (Institut Teknologi Sepuluh Nopember, 2017)
One program Surabaya City Government to repair the transport sector is build a mass transit rapid that one of them is a tram. The rapid development of mass transit is also expected to support the improvement of air quality in the city of Surabaya due to the effects of vehicle emissions. On of harmful vehicle emissions are Nox. One danger is the Nox can cause lung inflammation and paralysis. On the other hand, rapid mass transit development plan in Surabaya planned to use a portion of the road as the tram line. This will certainly reduce the capacity of roads. Therefore, a comparison between a reduction in the number of private vehicle users with the capacity reduction of the cost of air pollution in this case is the cost of Nox emissions into the topic of this research. The location of this research is Basuki Rahmat Street and Urip Sumoharjo Street which is one of the roads that traversed the tram line which is often congested. The method of calculating the amount of Nox based on the vehicle speed on the exixting condition and the condition of the plan. Based on calculations, the level of Nox reduction in the time before the tram operates when compared to when the tram operates on Urip Sumoharjo Street amounted 7.38%. While the level of Nox reduction in the time before the tram operates when compared to when the tram operates on Basuki Rahmat Street amounted to 11.81%. Then from the calculation of the cost air pollution, decrease the cost of air pollution due to Nox in Urip Sumoharjo Street is 9,185,321.87 rupiahs/year, while the decline in the cost of air pollution due to Nox in Basuki Rahmat Street is 14,664,554.40 rupiahs/year.